Analysis of kinematic movement characteristics of the common center of athlete's body mass while performing the crouch start - Liudmyla Shesterova; Valeriy Druz; Andriy Yefremenko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to determine the basic conditions for minimizing the cost of effort to accelerate the movement speed of the common center of athlete's body mass in the specified direction of his movement. Material & Methods: the study used video footage for short distances of the world's leading sprinters and athletes of various qualifications. To solve the problems, we used: a method for estimating the angles between biosigns and storyboard video, method of analogies, method of the theory of similarity and dimension, the method of computer modeling, statistical analysis, estimation of physical stress and strength impulse using the method of estimating the interdependence of the developed effort on the angle of expansion between the corresponding biokinematic links. Results: it sets the basic position kinematics movement common center of the athlete's body mass (CCM), which improves the efficiency of performance crouch start. The results of the dynamics of the movement of a common force vector are presented, which determines the direction of movement of the body's CCM in three-dimensional space, ensuring its movement along the center line of the run are presented. On the basis of the observed dynamics of the change in the direction of the resultant force vector, when a crouch start is performed, it is established that the trajectory of its movement is a helicoid. Conclusion: movement of the common center of body mass is carried out along the helicoid with subsequent reduction of its radius. Changes in the length of the helix forming the radius are systematic and reflect the energy efficiency of the running costs. The dynamics of the helicoidal movement of the generating vector is observed in each supporting phase of the running step, which makes it possible to assess the stability of the dynamic stereotype manifestation of the running step, and to judge by these indicators about the degree of athlete fatigue at the distance.